Pathways of Non-enzymatic Lysine Acylation - Baldensperger, Tim; Glomb, Marcus A. (Frontiers in Cell and Developmental Biology, 2021)
Posttranslational protein modification by lysine acylation is an emerging mechanism of cellular regulation and fine-tunes metabolic processes to environmental changes. In this review we focus on recently discovered pathways of non-enzymatic lysine acylation by reactive acyl-CoA species, acyl phosphates, and α-dicarbonyls. We summarize the metabolic sources of these highly reactive intermediates, demonstrate their reaction mechanisms, give an overview of the resulting acyl lysine modifications, and evaluate the consequences for cellular regulatory processes. Finally, we discuss interferences between lysine acylation and lysine ubiquitylation as a potential molecular mechanism of dysregulated protein homeostasis in aging and related diseases.